IDENTIFIKASI KOLEKTIF DAN IDEOLOGISASI JIHAD: - Gazi Saloom (Jurnal Dialog, 2015)
This article articulates that the terrorists in Indonesia are basically a group of normal people who have sound minds and a long-term goal to establish an Islamic government system based on the teachings of the Quran and Hadith. This study employed qualitative approach by acquiring the data through interviews, document analysis and media information covering terrorists and terrorism. A former terrorist involved in Bali bombing I served as the research informant. Data from in-depth interviews and document analysis were analyzed by utilizing social identity and social cognition theory about ideology of jihad. The article concludes that the changing process from the ordinary people into the terrorist strongly relates to jihad ideology and search for identity.